Pengaruh Financial Literacy, Penggunaan Investment Platform, dan Herding Behaviour Terhadap Keputusan Investasi pada Generasi Z di Jabodetabek - Maharani, Mutia; Takidah, Erika; Fauzi, Achmad (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of financial literacy, use of investment platforms, and herding behaviour on investment decisions among Generation Z in Jabodetabek. The method used in this research is a quantitative approach through instrument testing, classical assumption testing, hypothesis testing, and multiple linear regression analysis using SPSS 26. The accessible population in this study consists of 255 students, with a research sample of 156 students selected using proportionate stratified random sampling. The data used in this research is primary data obtained through questionnaires distributed via Google Forms. The results of the study conclude that: (1) the financial literacy variable has a positive effect on investment decisions; (2) the use of investment platform variable has a positive effect on investment decisions; (3) the herding behaviour variable has a positive effect on investment decisions; (4) the variables financial literacy, use of investment platform, and herding behaviour have a simultaneous influence on investment decisions.